2010
DOI: 10.1089/thy.2009.0457
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Preconception Thyrotropin Levels to Requirements for Increasing the Levothyroxine Dose During Pregnancy in Women with Primary Hypothyroidism

Abstract: We suggest that in women with hypothyroidism who are planning to become pregnant, serum TSH levels should be in the normal range but should not be greater than about 1.2 mIU/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 21 publications
0
36
0
6
Order By: Relevance
“…Others advocate that preconception TSH levels be lower than 1.2 mIU/L. In a study favoring the latter, only 17% of women with TSH values under this cutoff had to increase LT 4 dose later during pregnancy (58). Separate, however, from preconception TSH values, it is increasingly apparent that other factors can also influence the rapidity and extent of LT 4 augmentation necessary to maintain a euthyroid state during pregnancy.…”
Section: Question 9: Should Oh Be Treated In Pregnancy?mentioning
confidence: 99%
“…Others advocate that preconception TSH levels be lower than 1.2 mIU/L. In a study favoring the latter, only 17% of women with TSH values under this cutoff had to increase LT 4 dose later during pregnancy (58). Separate, however, from preconception TSH values, it is increasingly apparent that other factors can also influence the rapidity and extent of LT 4 augmentation necessary to maintain a euthyroid state during pregnancy.…”
Section: Question 9: Should Oh Be Treated In Pregnancy?mentioning
confidence: 99%
“…As shown in Table 1, these criteria unfortunately varied substantially among the available evidence. In this regard, it is worth noting that only Abalovich et al (21) referred to the same criteria used in our study. Interestingly, these authors reported a 32% rate of adjustment, markedly lower than the 84% observed in our series.…”
Section: Clinical Study a Busnelli And Others Levothyroxine Adjustmenmentioning
confidence: 92%
“…Both Abalovich et al (21) and Kothari & Girling (24) observed that, before pregnancy, the mean TSH value was lower in women who did not need additional L-T 4 during pregnancy than in those who needed an increase. Abalovich et al (21) also observed that only 17% of women with a preconception TSH lower than 1.2 mIU/l had to increase the L-T 4 dose during pregnancy (21). Inconsistency with our findings may be explained by a type 2 error.…”
Section: Clinical Study a Busnelli And Others Levothyroxine Adjustmenmentioning
confidence: 96%
“…Meanwhile it is reasonable practice to maintain TSH values in women planning pregnancy below 2.5 mU/l, especially in those with positive TPOAb; newly diagnosed patients should be treated in order to normalize maternal serum TSH values within the trimester-specific pregnancy reference range [89]. …”
Section: Effects Of Treatment Of Sch and Ih With Levothyroxinementioning
confidence: 99%